An Analysis of the Influence of Marketing Content Effectiveness and Customer Reviews on Purchase Intention at D'zuka Restaurant - Caroline Winona; Murhadi Murhadi; Dewi Ayu Kusumaningrum (Eduvest - Journal of Universal Studies, 2026)
In the modern era, the number of social media users continues to increase. Along with technological advancements, consumers no longer make purchasing decisions solely based on product attributes but also consider their digital experiences. Although marketing content and customer reviews are believed to play important roles in influencing purchasing decisions, the extent to which these factors directly affect purchase intention and how this relationship can be explained through the Elaboration Likelihood Model (ELM) theory require further investigation. This study aims to analyze the effects of marketing content effectiveness and customer reviews on purchase intention at D'zuka Restaurant, both partially and simultaneously, and to determine the magnitude of the influence of these variables on consumers’ purchase intentions. This study employed a quantitative research method by analyzing data obtained from questionnaire responses. The results showed that both independent variables had significant effects on purchase intention, with beta coefficients of 0.385 for marketing content effectiveness and 0.474 for customer reviews. Collectively, these two variables explained 61.3% of the variance in purchase intention (R² = 0.613). Both variables indicated information processing tendencies through the central and peripheral routes, with a stronger tendency toward the central route. These findings support the application of the Elaboration Likelihood Model theory in the context of social media and online review-based food marketing, demonstrating that both marketing content effectiveness and customer reviews significantly influence purchase intention, with customer reviews having a slightly stronger effect.